What's in a Name? Reputation Building and Corporate Strategy - Fombrun, Charles; Shanley, Mark (Academy of Management Journal, 1990)
Firms compete for reputational status in institutional fields. Managers attempt to influence other stakeholders' assessments by signaling firms' salient advantages. Stakeholders gauge firms' relative merits by interpreting ambiguous informational signals from the firms, the media, and other monitors. The results of an empirical study of 292 large U.S. firms supported the general hypothesis that publics construct reputations on the basis of information about firms' relative structural positions within organizational fields, specifically using market and accounting signals indicating performance, institutional signals indicating conformity to social norms, and strategy signals indicating strategic postures. Understanding the informational medium from which publics construct reputations helps explain sources of mobility barriers within industries that originate in external perceptions.